ETNOMATEMATIKA: TRADISI PENGUKURAN MASYARAKAT SUKU SASAK DAN POTENSI PENGINTEGRASIANNYA DALAM PEMBELAJARAN MATEMATIKA - Nur Hardiani; Susilahudin Putrawangsa (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
The focus of the current study is to investigate mathematical reasoning and behaviour among a local Indonesian tribe (Sasakese tribe in Lombok) in measurement tradition and their potential integration into mathematics instructions.  It is ethnomathematics research where the data are collected through observations, interviews, and artefact studies. The data are analyzed by using the qualitative-verificative approach. The findings indicate that Sasakese in Lombok performs mathematical reasoning and behaviour as a part of their tradition. In their measurement tradition, they have practised several mathematical principles. They have a conception about the role and the use of unit measurements. They have even invented several informal forms of unit measurements. They also have a conversion system of those unite measurements that are similar regarding mathematical principles to those of international standards, such as the metrics standard. They also show their understanding of the idea of ratio and proportion in utilizing the conversion system. Those mathematical traditions potentially inspire mathematics instructions. The tradition can be utilized as didactical phenomenology or as a mean to support students to reach more formal mathematics in teaching about unit measurement as well as ratio and proportion.